Huang-Lian-Jie-Du decoction treated sepsis via regulating ERK and SRC/STAT3 pathways and ameliorating metabolic status. Issue 92 (20th September 2016) - Liao, Shanting; Li, Pei; Wang, Junsong; Zhang, Qian; Xu, Dingqiao; Lv, Yan; Yang, Minghua; Kong, Lingyi
Abstract : LPS disturbed the metabolomic profiles and activated the ERK and SRC/STAT3 signaling pathways of mice, and HLJDD exerted therapeutic effects on sepsis induced by LPS. Abstract : Sepsis is a life-threatening disease in humans caused by a systemic inflammatory response, leading to high mortality. Huang-Lian-Jie-Du decoction (HLJDD) has been used to treat sepsis and improve its survival rate. In this investigation, a lipopolysaccharide (LPS)-induced mouse sepsis model was established and a 1 H NMR-based metabolomics approach complemented with survival rate studies, histopathological inspection, biochemical assays, mRNA expression analysis and western blot analysis was used to study the effects of HLJDD treatment on sepsis. LPS produced severe metabolic disturbance, including inflammation, oxidative stress, energy and amino acid metabolism, and it activated the ERK and SRC/STAT3 signaling pathways. HLJDD could greatly attenuate the disturbed metabolites and may exert its treatment effect by inhibiting the ERK and SRC/STAT3 signaling pathways.